THE DEVELOPMENT OF COLLABORATION SKILLS, TEAMWORK SKILLS AND CROSS-CULTURAL LEADERSHIP SKILLS FOR THE YOUTHS IN PAKROR SUB-DISTRICT, SONGKHLA PROVINCE - Nimsuwan, Nopadol; Prom-In, Sumet (Journal of Buddhist Anthropology, 2021)
The Objectives of this research article were to examine the effects of promoting collaboration skills, teamwork skills and cross-cultural leadership skills among young people in Pakror sub-district. This mixed method research The participants were 98 young people who participated in the training programme, "The development of collaboration skills, teamwork skill, and cross-cultural leadership skill for youth in Pakror sub-district”. The research tools were 1) the training programme and 2) the programme evaluation form. The data was analysed using percentage and mean values. The results of the programme evaluation showed that the majority of the participants agreed on the highest levels that the training programme provided the youth with the understanding of; principles of developing youth leadership skills ( = 4.39); the characteristics of creative, collaborative, and team work leadership ( = 4.62); the usage of information technology to support and develop leadership, collaborative, and teamwork skills ( = 4.46) and the ‘know-how’ to start inventing the project ( = 4.55). Additionally, the participants agreed, to some extent, that this project provided them with some various advantages in developing leadership skills. This is to say, the participants claimed that they had developed to be more assertive ( = 4.60), to build more self-confidence ( = 4.49), to be more empathetic ( = 4.41), to develop the teamwork skills ( = 4.56), to take more on responsibility ( = 4.46), to become more patient person ( = 4.37), to develop more positive human relation ( = 4.55), to have better problem solving skill ( = 4.43). Agreed on the highest level with the mean of 4.68, the participants claimed that they have grown more on public mind. Lastly, the participants’ overall satisfaction level was on highest level with the mean of 4.67. They also required the project to be held every year.